Studi Deskriptif: Determinan Teknologi, Informasi dan Komunikasi dalam Pengungkapan LKPD di Indonesia - Wiwin Juliyanti (Studi Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This descriptive study aims to explain technological determinants related to the disclosure of local government financial statements proxied in the variables of Telecommunications Network (X1), Internet Access (X2), Technology Development (X3), e-Government (X4), Website Accessibility (X5), Press Visibility (X6), and E-Procurement (X7) Method: A quantitative approach at the descriptive level is used in this study. The non-probability technique of the purposive sampling type obtained 450 observations from 150 samples of district local governments in Indonesia during 2017-2019 through documentation and literature review of secondary data. Data analysis using SPSS software. Results: The average level of telecommunications networks, quality of internet access, technology development, e-government, ease of website accessibility, and the frequency of procuring goods and services online for Indonesian local governments are in moderate numbers. Limitations: This study is only up to the level of describing the sample and using a limited number of ICT determinants. Some of the technological factor data used in this study are not detailed based on the district government, due to limited information obtained through the Ministry of Communication and Information and the Central Statistics Agency (BPS). Contribution: These findings contribute to central and regional governments as regulators and decision makers in formulating policies to consider technological factors related to financial report disclosure in order to realize transparency and public accountability in a time-effective and cost-efficient manner.